2009
DOI: 10.1038/aps.2009.110
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of angiotensin-converting enzyme (ACE) and ACE2 are not associated with orthostatic blood pressure dysregulation in hypertensive patients

Abstract: Aim: The genetic background of orthostatic blood pressure dysregulation remains poorly understood. Since the renin-angiotensin system plays an important role in blood pressure regulation and response to position change, we hypothesized that angiotensin-converting enzyme (ACE) and ACE2 genetic polymorphisms might contribute, at least partially, to orthostatic blood pressure dysregulation in hypertensive patients. Methods: Two tag single nucleotide polymorphisms (SNPs) of ACE2 and ACE I/D were genotyped in 3630 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 35 publications
5
35
3
1
Order By: Relevance
“…Because ACE and ACE2 act in counteracting ways (Crackower et al, 2002;Fan et al, 2009) we tested for any possible association, but, in our study no combined effect of ACE I/D and ACE2 rs2106809 polymorphisms was observed. Fan et al (2007), however, reported that ACE2 rs2106809 T allele when combined with the effect of the ACE DD genotype, increased the risk for hypertension by 2.34-fold in females.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…Because ACE and ACE2 act in counteracting ways (Crackower et al, 2002;Fan et al, 2009) we tested for any possible association, but, in our study no combined effect of ACE I/D and ACE2 rs2106809 polymorphisms was observed. Fan et al (2007), however, reported that ACE2 rs2106809 T allele when combined with the effect of the ACE DD genotype, increased the risk for hypertension by 2.34-fold in females.…”
Section: Discussioncontrasting
confidence: 68%
“…Chen et al (2010), in China, found the rs2106809 polymorphism to be associated with pulse pressure in women and men and with reduction in systolic blood pressure in women and also that it might act as an independent influencing factor of gene-gene interaction in BP reducing effects of benazepril. Fan et al (2009), however, did not find any significant association in either female or male Chinese patients with orthostatic hypertension. There are also some other studies on polymorphisms which did not show gender specification.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] However, the results from these studies were inconsistent.…”
Section: Introductionmentioning
confidence: 68%